THE ROLE OF ECONOMY IN UZBEKISTAN - Umataliyev Farruxbek Umarjon o’g’li (Modern American Journals, 2025)
This article gives his views and comments on the position of economy in the Republic of Uzbekistan, its prospects.
Keywords: Economy, development, state, management, finance, money, world market.